Osteochondral Allograft and High Tibial Osteotomy With Patient-Specific Instrumentation - Ryan Selley MD; Thun Itthipanichpong MD; Samarth Venkata Menta BA; Anil S. Ranawat MD (SAGE Publishing, 2023)
Background: Medial compartment osteoarthritis in young active patients presents a unique challenge with regard to joint preservation. Interventions, including cartilage restoration procedures, in the setting of high tibial osteotomy (HTO) have the potential to obviate or delay joint replacement if performed with a high degree of accuracy and avoidance of complications. Indications: The procedure is indicated in patients less than 65 years with isolated medial knee arthrosis, good range of motion, and no ligamentous instability. Technique Description: We present our technique for valgus producing opening wedge HTO with patient-specific instrumentation and implant with concomitant osteochondral allograft of the medial femoral condyle and tibial microfracture. Results: The goal of this intervention is to provide a minimally painful knee with durable (>10 year) outcome while minimizing the risk of perioperative complications including iatrogenic fracture and nonunion. Discussion/Conclusion: High tibial osteotomy with concomitant cartilage repair techniques can lead to high satisfaction and return to sport rates in appropriately selected patients. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.